Enhanced functional characteristics as a cholesterol-lowering bioactive peptide from Kara Kratok sprouts (Phaseolus lunatus L.) - Budiyanto, Cahyo; Ningrum, Andriati; Murdiati, Agnes; Indrati, Retno (Penerbit Universiti Kebangsaan Malaysia, 2025)
HMG-CoA reductase is an enzyme that converts HMG-CoA into cholesterol via the mevalonate pathway, contributing to cardiovascular disease. The germination of brown kara kratok (Phaseolus lunatus) mixtures, including dark brown, light brown, or brown color pattern, specifically for 0, 24, 48, 72, and 96 h, yielded interesting results. The samples were measured for radicle length, % inhibition of HMG-CoA reductase, type of inhibition, IC50 value, total protein content, amino acids, percentage degree of hydrolysis (%DH), and molecular weight (MW), providing valuable insights into the potential use of these biopeptides. The results showed that biopeptides from germinated kara kratok exhibited the ability as HMG-CoA reductase inhibitors. Furthermore, the germination process increased its capability, from 46.79% in beans to 83.77% in 72-h germination. The 72-h germination was observed to be the best HMG-CoA reductase inhibitor as a competitive inhibitor, with an IC50 value of 335.09 μg/mL. This was supported by a total protein content of 27.76%, with glutamic acid (2.99%) as the dominant amino acid, followed by phenylalanine, aspartic acid, leucine, serine, and arginine, %DH (26.26%), and MW (5-15 kDa). Brown kara kratok sprouts possess the potential to inhibit HMG-CoA reductase, and germination increases its capability.